2022
DOI: 10.1007/s12209-022-00325-y
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Support Interactions on Ag/Co3O4 Nanowire Monolithic Catalysts Promoting Catalytic Soot Combustion

Abstract: Tuning metal–support interactions (MSIs) is an important strategy in heterogeneous catalysis to realize the desirable metal dispersion and redox ability of metal catalysts. Herein, we use pre-reduced Co3O4 nanowires (Co-NWs) in situ grown on monolithic Ni foam substrates to support Ag catalysts (Ag/Co-NW-R) for soot combustion. The macroporous structure of Ni foam with crossed Co3O4 nanowires remarkably increases the soot–catalyst contact efficiency. Our characterization results demonstrate that Ag species exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
(62 reference statements)
1
5
0
Order By: Relevance
“…From the HRTEM images in Figure 3a3–d3, the Co 3 O 4 phase with the lattice plane (311) is observed in all catalysts, [22,32] which is highly consistent with the XRD results. No crystal planes containing Mn species were observed, suggesting Mn was doped into the lattice of Co 3 O 4 forming Co−Mn solid solution combining with the XRD results [25] …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…From the HRTEM images in Figure 3a3–d3, the Co 3 O 4 phase with the lattice plane (311) is observed in all catalysts, [22,32] which is highly consistent with the XRD results. No crystal planes containing Mn species were observed, suggesting Mn was doped into the lattice of Co 3 O 4 forming Co−Mn solid solution combining with the XRD results [25] …”
Section: Resultssupporting
confidence: 83%
“…Cobalt and manganese oxides have many advantages among common non-noble metal materials, such as variable valent states and excellent low-temperature redox performance, [17][18][19] so they are widely used in catalytic oxidation reactions. [20][21][22][23] Additionally, extensive studies have elucidated that the synergistic effect of cobalt and manganese oxides exhibits higher redox properties than single metal oxides due to the formation of solid solutions. [24][25][26][27][28] Therefore, the strategy of introducing Mn species into Co 3 O 4 phase to construct CoMnO nano-composites would effectively improve redox properties for the soot oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve base-free HMF oxidation to FDCA, the basic metal oxides such as HAP, CeO 2 , ZrO 2 , MgO, Co 3 O 4 , , and supported noble-metal nanoparticle catalysts have been widely explored. The strong metal–support interaction plays a crucial role in influencing the structure and electronic properties of noble-metal nanoparticles, thus enhancing catalytic performance. Through chemical bonding and electron transfer between the metal and oxide, the activity of active sites can be improved, enabling precise control over catalytic performance . For instance, Gao et al reported Ru nanoparticles supported on Mn–Ce mixed oxides (Ru/Mn X Ce 1 O Y ) with enhanced oxygen mobility and strong metal–support interaction, applied in the aerobic oxidation of HMF to FDCA without the addition of any base additives, leading to an exceptional FDCA yield of 99%.…”
Section: Introductionmentioning
confidence: 99%
“…Diesel engines are widely used in heavy vehicles because of their low operating costs, good durability, and reliable operation under lean conditions [ 1 ]. Although diesel engines and gasoline direct-injection engines (GDI) improve fuel efficiency, the emissions of exhaust gases including NO x and particulate matter (PM), lead to severe environmental pollution and human hazards [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%